Alloreactive cytolytic T cell clones with dual recognition of HLA-B27 and HLA-DR2 antigens. Selective involvement of CD8 in their class I-- directed cytotoxicity (The Rockefeller University Press, 1987)
HLA-B27- responder cells were stimulated in vitro with HLA-B27.1+ lymphoblastoid cell lines, and alloreactive CTL clones were obtained by limiting dilution. Three of these clones specifically lysed B27.1+ targets. In addition, they also lysed homozygous DR2 targets with various degrees of efficiency, depending on the Dw specificity of the target cell. All three clones possessed a homogeneous CD3+,CD8+,CD4- phenotype and were also homogeneous upon subcloning. Cold-target inhibition analyses showed mutual inhibition of B27.1 target lysis by DR2 targets and vice versa. Lysis of B27.1 targets was selectively inhibited by anti-class I mAbs. In contrast, lysis of DR2 targets was inhibited only by anti-class II and anti-DR monomorphic antibodies, but not by anti-class I, anti-DQw1, or anti-DP antibodies. The results indicate that these clones display dual recognition for HLA-B27.1 and for HLA-DR2 and suggest that HLA-B27.1 may share at least one epitope that is closely related to some stimulatory Dw determinants present on the HLA-DR2 antigens. Lysis of both B27+ and DR+ targets was inhibited by an anti-CD3 mAb. In contrast, an anti-CD8 antibody selectively inhibited the B27- but not the DR2-directed killing by these clones. The data support a stabilizing role of CD8 through its binding to the same class I (but not class II) molecule on the target cell bound by the T cell antigen receptor.